2016
DOI: 10.1002/gps.4578
|View full text |Cite
|
Sign up to set email alerts
|

Disability in prison activities of daily living and likelihood of depression and suicidal ideation in older prisoners

Abstract: Identifying older prisoners who have difficulty performing PADLs may help distinguish prisoners who may also be likely to be depressed or experience more severe SI. Furthermore, the association between PADL disability and depression may be particularly salient in older male prisoners. Longitudinal studies are needed as causal inferences are limited by the cross-sectional design. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 47 publications
1
40
0
1
Order By: Relevance
“…Suicide is a major problem across the lifespan; yet, internationally, rates are consistently highest among middleaged and older adults (see Fiske & O'Riley, 2016;Lutz, Morton, Turiano, & Fiske, 2016;Stanley, Hom, Rogers, Hagan, & Joiner, 2016; World Health Organization (WHO), 2014), which is a trend that remains relatively stable across differing sociological settings (see Stanley et al, 2016; see also Nock et al, 2008; World Health Organization (WHO), 2014). Indeed, in the United States, older prisoners exhibit the highest rates of suicide in correctional systems (Barry, Wakefield, Trestman, & Conwell, 2017;Carson & Cowhig, 2020;Noonan, Rohloff, & Ginder, 2015). Despite that suicide in later life has become a major public health issue, there has been limited scholarly and public attention devoted to suicidality among older adults (Lutz et al, 2016;Van Orden & Deming, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Suicide is a major problem across the lifespan; yet, internationally, rates are consistently highest among middleaged and older adults (see Fiske & O'Riley, 2016;Lutz, Morton, Turiano, & Fiske, 2016;Stanley, Hom, Rogers, Hagan, & Joiner, 2016; World Health Organization (WHO), 2014), which is a trend that remains relatively stable across differing sociological settings (see Stanley et al, 2016; see also Nock et al, 2008; World Health Organization (WHO), 2014). Indeed, in the United States, older prisoners exhibit the highest rates of suicide in correctional systems (Barry, Wakefield, Trestman, & Conwell, 2017;Carson & Cowhig, 2020;Noonan, Rohloff, & Ginder, 2015). Despite that suicide in later life has become a major public health issue, there has been limited scholarly and public attention devoted to suicidality among older adults (Lutz et al, 2016;Van Orden & Deming, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Despite that suicide in later life has become a major public health issue, there has been limited scholarly and public attention devoted to suicidality among older adults (Lutz et al, 2016;Van Orden & Deming, 2018). Much less is known about the nature of suicidal thoughts and attempts among older prisoners (see Barry et al, 2017), especially with respect to how older prisoners compare to younger counterparts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the medical literature about criminal justice-involved older adults in the U.S. is sparse, research has shown many experience disproportionate rates of co-occurring behavioral, medical and mental health conditions (Barry et al, 2016, Bolano et al, 2016, Chodos et al, 2014). As a result, criminal justice, health, and social service professionals interact with these individuals on a frequent basis (Brown et al, 2014, Soones et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…On an international level, research has focused specifically on the incidence of physical and mental diseases 5,6 , analysis of inmate needs 7 and on problems of adaptation to the prison environment [8][9][10] . Few research studies have focused on variables such as stress and depression (see review 11 ), suicide 12,13 or the symptoms of posttraumatic stress 14 . Nor is there are any research on wellbeing, psychological resources or the presence of positive emotions presented by older inmates.…”
Section: Introductionmentioning
confidence: 99%